Palladium-catalysed atom-economical synthesis of conjugated dienals from terminal acetylenes and acrolein. Issue 45 (22nd May 2017) - Hearne, Zoë; Li, Chao-Jun
Abstract : Conjugated ( E, E )-dienals are versatile synthetic intermediates which can be readily prepared in two steps from simple, unactivated starting materials. Abstract : Conjugated ( E, E )-dienals are versatile synthetic intermediates owing to their trifunctional, electrophilic nature and the prevalence of the ( E, E )-diene in a wide range of functional molecules. It is shown herein that ( E, E )-dienals can be readily prepared in two palladium-catalysed steps from simple, unactivated starting materials; terminal acetylenes and acrolein can be coupled via conjugate addition, followed by alkyne isomerisation. This procedure provides a highly atom-economical, redox-neutral and practical method to prepare a range of conjugated ( E, E )-dienals in good yields and diastereoselectivities.